Economic AI on the move: the relationship between sugar-sweetened beverages consumption and weight gain in Kyrgyzstan - Suyunov, Alisher; Akramov, Kamiljon T. (Informa UK Limited, 2024)
The prevalence of overweight and obesity has been increasing in Central Asia. Among numerous potential dietary determinants of overweight and obesity, sugar-sweetened beverages (SSBs) have received a great deal of attention because they are a significant source of calories and added sugars in both children and adults. In this study, we examine the relationship between SSB consumption and overweight and obesity in Kyrgyzstan using household-level data from the Kyrgyzstan Integrated Household Survey 2011 using propensity score matching in tandem with machine-learning models. The findings of our study indicate SSBs consumption is associated with 1.6 percentage point higher risk of obesity among both men and women in the context of Kyrgyzstan. Besides, we have observed the positive association between age, income, calorie intake, and share of calorie intake from staples and the likelihood of being obese.